"Crowding in" and the Returns to Government Investment in Low-Income Countries - Eden, Maya (World Bank, Washington, DC, 2014)
This paper estimates the effect of government investment on private investment in a sample of 39 low-income countries. Fluctuations in a predetermined component of disbursements on loans from official creditors to developing country governments are used as an instrument for fluctuations in public investment. The analysis finds evidence of "crowding in": an extra dollar of government investment raises private investment by roughly two dollars, and output by 1.5 dollars. To understand the implications for the return to public investment, a CES production function with public and private capital as inputs is calibrated. For most countries in the sample, the returns to government investment exceed the world interest rate. However, for some countries that already have high government investment rates, the return to further investment is below the world interest rate.